2017
DOI: 10.1159/000478899
|View full text |Cite
|
Sign up to set email alerts
|

Application of BI-RADS Descriptors in Contrast-Enhanced Dual-Energy Mammography: Comparison with MRI

Abstract: Background: Contrast-enhanced (CE) magnetic resonance imaging (MRI) BI-RADS descriptors are used in the evaluation of contrast-enhanced dual-energy mammography (CEDEM) images of mass lesions and are assumed to be applicable. Patients and Methods: Patients with suspicious mass lesions on mammography (BI-RADS 4 or 5) were included. CEDEM examinations were performed using a modified prototype unit. CE-MRI was performed using a high temporal and high spatial resolution imaging protocol. 2 blinded breast radiologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 28 publications
2
21
0
1
Order By: Relevance
“…Also in our study, non-mass internal enhancement pattern as a clumped pattern (3 cases were detected all proven to be malignant) and heterogeneous pattern as 9 of (12 cases proven to be malignant) showed high prediction probability of malignancy. Following Kamal et al 20 who concluded that segmental, ductal and regional clumped or heterogeneous enhancement was significantly associated with malignant lesions. If subtle architectural distortion was seen on mammography, the underlying lesion can be demonstrated on CEDM.CEDM could detect 32 enhancing mass with descriptive morphology of its shape, margin and enhancement pattern all masses were proven as malignancy.…”
Section: Mass Enhancementmentioning
confidence: 99%
See 2 more Smart Citations
“…Also in our study, non-mass internal enhancement pattern as a clumped pattern (3 cases were detected all proven to be malignant) and heterogeneous pattern as 9 of (12 cases proven to be malignant) showed high prediction probability of malignancy. Following Kamal et al 20 who concluded that segmental, ductal and regional clumped or heterogeneous enhancement was significantly associated with malignant lesions. If subtle architectural distortion was seen on mammography, the underlying lesion can be demonstrated on CEDM.CEDM could detect 32 enhancing mass with descriptive morphology of its shape, margin and enhancement pattern all masses were proven as malignancy.…”
Section: Mass Enhancementmentioning
confidence: 99%
“…They make use of contrast injection to acquire good-quality images and achieve a proper diagnostic performance, aiming adequate morphological assessment. 20 According to the 5th edition of the ACR BI-RADS Atlas, there is a well-defined and standardized lexicon of morphology descriptors to characterize breast lesions on DCE-MRI; yet, there is no similar lexicon for CEDM. The need for a standardized lexicon of morphology descriptors has become essential to analyze and report enhancing lesions identified on CEDM.…”
Section: Mass Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…Knogler et al used BI-RADS descriptors of contrast enhanced magnetic resonance imaging for the assessment of contrast enhanced dual energy mammography mass lesion images. 11 women with suspicious mass lesions on their mammograms (BI-RADS 4 or 5) were included [97]. The contrast enhanced dual energy mammography images were obtained from a modified Siemens Mammomat Inspiration unit (Siemens Healthcare) ( Figure 5c).…”
Section: Clinical Practicementioning
confidence: 99%
“…The added value of DBT to mammography in BI-RADS assessment and follow-up management is investigated by Galati et al [51]. Knogler et al [52] present results on CEDM for breast lesion detection, characterization and comparison to DCE-MRI. The potential of DCE-MRI including quantitative pharmacokinetic modeling for the assessment and prediction of response to neoadjuvant chemotherapy in breast cancer overall (Dietzel et al [53]) and with a special focus on inflammatory breast cancer (van Uden et al [54]) is discussed.…”
mentioning
confidence: 99%